Decolonization of Islamic Education and Efforts to Achieve Academic Independence: A Case Study of Ma'had Aly Lirboyo Kediri - Ubaidila, Syafik; Sulaeman, Mubaidi; Khamim; Djamaludin, Burhan (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This study aims to examine how Ma’had Aly Lirboyo implements epistemological decolonization in Islamic education through the preservation of pesantren traditions and their integration into the formal higher education system. The background of this research is rooted in the dominance of Western epistemology within national education systems, which often marginalize the Islamic intellectual heritage. This is a field research study using a qualitative approach, employing techniques such as direct observation, in-depth interviews with Ma’had Aly administrators and educators, and documentation analysis of institutional policies and curricula. The findings reveal that Ma’had Aly Lirboyo successfully preserves traditional pesantren methods—such as bandongan, sorogan, wetonan, and daurah ilmiah—while adapting them to a structured academic system through the Fiqh Kebangsaan curriculum. This strategy has enabled the development of an Islamic education model that not only maintains sanad (chains of knowledge transmission) and scholarly authority but also responds effectively to national and global challenges. Theoretically, these findings reinforce the discourse of knowledge decolonization by demonstrating that local systems of knowledge—rooted in tradition, spirituality, and social context—can form legitimate, autonomous, and globally relevant educational frameworks.